Remediation of textile effluents by membrane based treatment techniques: A state of the art review. (1st January 2015) - Dasgupta, Jhilly; Sikder, Jaya; Chakraborty, Sudip; Curcio, Stefano; Drioli, Enrico
Abstract: The textile industries hold an important position in the global industrial arena because of their undeniable contributions to basic human needs satisfaction and to the world economy. These industries are however major consumers of water, dyes and other toxic chemicals. The effluents generated from each processing step comprise substantial quantities of unutilized resources. The effluents if discharged without prior treatment become potential sources of pollution due to their several deleterious effects on the environment. The treatment of heterogeneous textile effluents therefore demands the application of environmentally benign technology with appreciable quality water reclamation potential. These features can be observed in various innovative membrane based techniques. The present review paper thus elucidates the contributions of membrane technology towards textile effluent treatment and unexhausted raw materials recovery. The reuse possibilities of water recovered through membrane based techniques, such as ultrafiltration and nanofiltration in primary dye houses or auxiliary rinse vats have also been explored. Advantages and bottlenecks, such as membrane fouling associated with each of these techniques have also been highlighted. Additionally, several pragmatic models simulating transport mechanism across membranes have been documented. Finally, various accounts dealing with techno-economic evaluation of these membrane based textile wastewater treatment processes have been provided. Highlights: Role of membrane technology in textile effluent treatment is critically reviewed. Parameters and product quality of different membrane techniques are discussed. Loopholes in membrane technology are identified. Simulations of membrane based textile wastewater treatment methods are summarized. Techno-economic evaluation studies on these membrane based processes are appraised.